Comparative Effectiveness of Mesalamine, Sulfasalazine, Corticosteroids, and Budesonide for the Induction of Remission in Crohn's Disease: A Bayesian Network Meta-analysis. Issue 5 (May 2017) - Coward, Stephanie; Kuenzig, M. Ellen; Hazlewood, Glen; Clement, Fiona; McBrien, Kerry; Holmes, Rebecca; Panaccione, Remo; Ghosh, Subrata; Seow, Cynthia H.; Rezaie, Ali; Kaplan, Gilaad G.
Abstract : Background: Induction treatment of mild-to-moderate Crohn's disease is controversial. Purpose: To compare the induction of remission between different doses of mesalamine, sulfasalazine, corticosteroids, and budesonide for active Crohn's disease. Data sources: We identified randomized controlled trials from existing Cochrane reviews and an updated literature search in Medline, EMBASE, and CENTRAL to November 2015. Study selection: We included randomized controlled trials (n = 22) in adult patients with Crohn's disease that compared budesonide, sulfasalazine, mesalamine, or corticosteroids with placebo or each other, for the induction of remission (8–17 wks). Mesalamine (above and below 2.4 g/d) and budesonide (above and below 6 mg/d) were stratified into low and high doses. Data extraction: Our primary outcome was remission, defined as a Crohn's Disease Activity Index score <150. A Bayesian random-effects network meta-analysis was performed on the proportion in remission. Data synthesis: Corticosteroids (odds ratio [OR] = 3.64; 95% credible interval [CrI]: 2.16–6.19), high-dose budesonide (OR = 2.99; 95% CrI: 1.83–4.90), and high-dose mesalamine (OR = 1.87; 95% CrI: 1.14–3.15) were superior to placebo. Corticosteroids were similar to high-dose budesonide (OR = 1.21; 95% CrI: 0.79–1.89), but more effective than high-dose mesalamine (OR = 1.95; 95% CrI: 1.14–3.25). Sulfasalazine was not significantly superior to any therapy including placebo. Limitations: Randomized controlled trials that use a strict definition of induction of remission and disease severity at enrollment to assess effectiveness in treating mild-to-moderate Crohn's disease are limited. Conclusions: Corticosteroids and high-dose budesonide were effective treatments for inducing remission in mild-to-moderate Crohn's disease. High-dose mesalamine maybe an option among patients preferring to avoid steroids. Abstract : Supplemental Digital Content is Available in the Text.Article first Published online 31 January 2017